Nuclear Medicine in Endocrine Disorders Diagnosis and Therapy - Coura-Filho, George Barberio; Torres Silva de Oliveira, Mayara; Morais de Campos, Ana Luiza; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents up-to-date information on the general principles of diagnostic and therapeutic nuclear medicine in the context of endocrinology. The content is divided into six parts. Section I examines general aspects of radiopharmaceuticals, scintigraphy, single-photon emission computed tomography (SPECT), positron emission tomography (PET), radionuclide therapies and radioguided surgery. Section II discusses diagnostic applications in benign thyroid diseases and evaluation of thyroid nodules. Section III gives an overview of the management of parathyroid diseases. Section IV presents diagnostic techniques in well-differentiated thyroid cancer. Section V addresses procedures and therapy in adrenal benign and malignant disorders (phaechromocytomas and paragangliomas). Lastly, the diagnosis and treatment of neuroendocrine tumors are featured in Section VI. Nuclear Medicine in Endocrine Disorders: Diagnosis and Therapy is intended for non-specialists in nuclear medicine working in the field of endocrinology, and is also a valuable resource for researchers and students.
Radiopharmaceuticals Definitions -- Principles of Scintigraphies -- Principles of Single Photon Emission Tomography -- Principles of Positron Emission Tomography -- Principles of Nuclear Medicine Therapies -- Diagnostic Nuclear Medicine in Hyperparathyroidism -- Diagnostic Nuclear Medicine in Hyperthyroidism -- Diagnostic Nuclear Medicine in Well Differentiated Thyroid Cancer -- Diagnostic Nuclear Medicine in Medullary Thyroid Carcinoma -- Diagnostic Nuclear Medicine in Pheochromocytomas and Paragangliomas -- Diagnostic Nuclear Medicine in Pulmonary, Intestinal and Pancreatic Neuroendocrine Tumors -- Diagnostic Nuclear Medicine in Parathyroid Carcinomas -- Diagnostic Nuclear Medicine in Multiple Endocrine Neoplasia Syndromes -- Therapeutic Nuclear Medicine in Hyperthyroidism -- Therapeutic Nuclear Medicine in Well Differentiated Thyroid Cancer -- Therapeutic Nuclear Medicine in Pheochromocytomas and Paragangliomas -- Therapeutic Nuclear Medicine in Pulmonary, Intestinal and Pancreatic Neuroendocrine Tumors -- Intraoperative Radioguided Localization of Parathyroids -- Intraoperative Radioguided Localization of Sentinel Node in Thyroid Cancer.
Keywords: Radiology; Internal medicine; Endocrine glands; Radiology; Internal Medicine; Endocrine System; Endocrine System Diseases -- diagnosis; Endocrine System Diseases -- therapy; Nuclear Medicine